1996
DOI: 10.1046/j.1365-2222.1996.d01-281.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pityrosporum orbiculare reactive T cells from skin and blood in atopic dermatitis and characterization of their cytokine profiles

Abstract: Our data suggest that P. orbiculare can induce a T-cell response in AD patients. The Th2-like profile of P. orbiculare-reactive TCC derived from lesional skin indicates that P. orbiculare may play a role in maintaining IgE-mediated skin inflammation in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…Allergen specific T cells cloned from acute AEDS lesional skin show a Th2/Th0-like cytokine profile [64, 72], while the in situ expression of IL-4 in chronic AEDS lesions is accompanied by the expression of interferon-γ [73, 74], also suggesting an involvement of Th1 cytokines in the chronic phase. A possible scenario would be an influence by Th2 cytokines from allergen-specific T cells in the acute phase of AEDS.…”
Section: Possible Pathogenic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergen specific T cells cloned from acute AEDS lesional skin show a Th2/Th0-like cytokine profile [64, 72], while the in situ expression of IL-4 in chronic AEDS lesions is accompanied by the expression of interferon-γ [73, 74], also suggesting an involvement of Th1 cytokines in the chronic phase. A possible scenario would be an influence by Th2 cytokines from allergen-specific T cells in the acute phase of AEDS.…”
Section: Possible Pathogenic Mechanismsmentioning
confidence: 99%
“…Elevated proliferation of PBMC in response to in vitro stimulation with Malassezia extract has been found in AEDS patients with specific serum IgE to Malassezia [16, 64, 65, 66]in combination with a Th2-like cytokine profile [65, 66, 67]. The Th2-like cytokines IL-4 and IL-13 support IgE production, while IL-5 promotes growth and differentiation of eosinophils [68], one of the early skin-infiltrating cells in the APT reaction [21, 69].…”
Section: Possible Pathogenic Mechanismsmentioning
confidence: 99%
“…Recently, it has been shown that both the acute and chronic AD lesions are associated with an increased expression of IL-13 mRNA when AD skin biopsy specimens were compared with those from normal control subjects using in situ hybridization [12]. Furthermore, it has been shown that IL-13 mRNA is detected in PBMC from patients with AD [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Many reports clearly indicate the role of Malassezia in AD, especially AD located to the head and neck area in adults (19,26,29,30,41,62,66,69,74,83,98,109,125,131,132,135,136,137,148,149,154). The Malassezia yeasts have been cultured from patients with AD with the same frequency as from healthy individuals (19,41,52).…”
Section: Atopic Dermatitis and The Malassezia Yeastsmentioning
confidence: 99%
“…Several IgE binding components of Malassezia have been isolated (29,30,62,66,69,70,98,131,132,137,149,157,166,167). Three major allergen components from Malassezia were later identified using monoclonal antibodies (166).…”
Section: Atopic Dermatitis and The Malassezia Yeastsmentioning
confidence: 99%